Reduction behavior of iron in the red mud - Eray S.; Keskinkilic E.; Topkaya Y.A.; Geveci A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Red mud or bauxite residue contains significant quantities of industrial metals such as Fe, Al, and Ti, as well as rare earth elements such as Sc, Ce, and La. The authors performed a laboratory-scale project dealing with stepwise recovery of valuable elements from two bauxite residues, namely Iranian red mud (IRM) and Turkish red mud (TRM). The first stage involved the recovery of iron which was present in large quantities in red mud. Two different methods were investigated for this purpose: 1) solid state reduction followed by wet magnetic separation and 2) smelting. In the scope of this paper, some results of pyrometallurgical part of this project are presented. According to solid-state reduction experiments, it was found that more excess coal was needed for IRM (35%) than for TRM (15%) to maximize iron reduction. Temperature had significant effect on the reduction process and metallization increased from about 70% to about 95% when the temperature was raised from 1000 to 1200°C. Metallization degree was reported to be slightly higher for IRM (96.2%) than for TRM (94.1%). The results demonstrated that a high degree of iron metallization can be achieved regardless of the chemical and mineralogical composition of the bauxite residue sample.